128k views
3 votes
Solve for x: -4(3x − 2) = 6x + 2

User MarcWan
by
4.9k points

2 Answers

1 vote

Answer:


x=(1)/(3)

Explanation:


\text{We're given the following:}\\-4(3x-2)=6x+2\\\\\text{First, let's distribute the -4:}\\-12x+8=6x+2\\+12x\qquad+12x\\\\\text{That gives us:}\\8=18x+2\\-2\qquad-2\\6=18x\\\\\text{Now divide both sides by 18:}\\(6)/(18)=x\\\\\text{And simplify the fraction:}\\x=(1)/(3)

User Kdauria
by
5.2k points
2 votes

Answer:

x = 1/3

Explanation:

-4(3x − 2) = 6x + 2

Distribute

-12x +8 = 6x +2

Add 12x to each side

12x-12x+8 = 6x+2+12x

8 = 18x+2

Subtract 2 from each side

8-2 = 18x+2-2

6 = 18x

Divide each side by 18

6/18 = 18x/18

1/3 =x

User Mthmulders
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.